Influence of New FIGO 2018 Staging on Treatment Outcomes in Early-Stage Cervical Cancer: A Single-Center Study - Kaur, Satinder; Garg, Hemlata; Nandwani, Megha; Kalita, Manoj; Bansal, Satish; Singh, Randeep (South Asian Journal of Cancer, 2022)
Purpose The aim of this article was to study survival outcomes of early-stage cervical cancer patients and impact on survival after restaging them as per International Federation of Gynecology and Obstetrics (FIGO) 2018.Materials and Methods A retrospective study was conducted from June 1, 2013 to May 31, 2018 in a tertiary care hospital in North India. One-hundred patients of early-stage cervical cancer (as per FIGO 2009 staging) who had been treated by surgery followed by risk based tailored adjuvant therapy in our hospital were evaluated. The clinicopathological features and survival outcomes of these patients were analyzed. These patients were then restaged as per new FIGO 2018 staging and survival outcomes between two FIGO classifications were compared.Results The median age of the study population was 52.5 years with median follow-up of 62.1 months. Ninety percent of our patients had more than 2 years follow-up and 59% had more than 5 years follow-up. The overall survival and relapse-free survival were 87.5 and 91.4%, respectively. The study population was then reclassified according to new FIGO 2018 staging. It was seen that the patients with stage IB1and IB2 cervical cancer had overall survival of 91.1 and 90%, respectively. The overall survival of stage IB3 was 80% and the survival of stage IIIC1 was only 60%.Conclusion The new FIGO 2018 classification has a significant effect on survival outcome and in prognostication of patients with cervical cancer.
Keywords: early stage cervical cancer; FIGO staging